2021
DOI: 10.3389/fonc.2020.597476
|View full text |Cite
|
Sign up to set email alerts
|

Only Tumors Angiographically Identified as Hypervascular Exhibit Lower Intraoperative Blood Loss Upon Selective Preoperative Embolization of Spinal Metastases: Systematic Review and Meta-Analysis

Abstract: BackgroundThe role of preoperative embolization (PE) in reducing intraoperative blood loss (IBL) during surgical treatment of spinal metastases remains controversial.MethodsA systematic search was conducted for retrospective studies and randomized controlled trials (RCTs) comparing the IBL between an embolization group (EG) and non-embolization group (NEG) for spinal metastases. IBL data of both groups were synthesized and analyzed for all tumor types, hypervascular tumor types, and non-hypervascular tumor typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…[ 4 ] Several studies have indicated that patients who undergo PE experience surgical and clinical benefits compared to patients who did not undergo PE. [ 2 , 11 - 13 ] Complete embolization can be achieved in 50-86% of patients. [ 4 ] Incomplete embolization can occur due to the presence of nearby radiculomedullary arteries, the inability to selectively catheterize feeding arteries, and intratumoral arteriovenous shunting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 4 ] Several studies have indicated that patients who undergo PE experience surgical and clinical benefits compared to patients who did not undergo PE. [ 2 , 11 - 13 ] Complete embolization can be achieved in 50-86% of patients. [ 4 ] Incomplete embolization can occur due to the presence of nearby radiculomedullary arteries, the inability to selectively catheterize feeding arteries, and intratumoral arteriovenous shunting.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Studies have demonstrated that intraoperative blood loss in the embolization group is significantly reduced compared to the non-embolization group. [ 2 , 11 , 13 , 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations